2018
DOI: 10.1186/s12862-018-1164-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the benefits of horizontal gene transfer by laboratory evolution and genome sequencing

Abstract: BackgroundRecombination is widespread across the tree of life, because it helps purge deleterious mutations and creates novel adaptive traits. In prokaryotes, it often takes the form of horizontal gene transfer from a donor to a recipient bacterium. While such transfer is widespread in natural communities, its immediate fitness benefits are usually unknown. We asked whether any such benefits depend on the environment, and on the identity of donor and recipient strains. To this end, we adapted Escherichia coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 104 publications
(129 reference statements)
1
20
0
Order By: Relevance
“…Our results also suggest native soil and marine microbial communities will continue to carry synthetic vectors with useful catabolic genes, likely until the metabolic cost of replicating the vector no longer presents an advantage. This agrees with previous studies which show that HGT transfer events that alter organism metabolism can increase organism fitness by allowing them to colonize new ecological niches 57,60,61 . It also suggests that this approach to engineering polluted ecosystems is self-limiting: selective pressure from the existing ecosystem could remove introduced genes from local microbial populations when no longer needed.…”
Section: Vector-exchange Between E Coli Dh5α and Indigenous Bacteriasupporting
confidence: 93%
“…Our results also suggest native soil and marine microbial communities will continue to carry synthetic vectors with useful catabolic genes, likely until the metabolic cost of replicating the vector no longer presents an advantage. This agrees with previous studies which show that HGT transfer events that alter organism metabolism can increase organism fitness by allowing them to colonize new ecological niches 57,60,61 . It also suggests that this approach to engineering polluted ecosystems is self-limiting: selective pressure from the existing ecosystem could remove introduced genes from local microbial populations when no longer needed.…”
Section: Vector-exchange Between E Coli Dh5α and Indigenous Bacteriasupporting
confidence: 93%
“…Bacterial asexual reproduction leads to clonal interference, preventing many beneficial mutations from reaching fixation within the evolving populations. Chu et al investigated induced horizontal gene transfer as a method to speed adaptation and circumvent clonal interference, and found that genetic exchange between distinct cocultured E. coli strains could significantly aid in adaptation to growth on novel carbon sources, contingent on the specifics of donor vs. host strain similarity and evolutionary environment (Chu et al, 2018). Contrasting with horizontal gene transfer, another technique to increase the accessibility of adaptive mutations is simply to increase the mutation rate, which can be induced with chemical mutagens (Lee et al, 2011) or naturally result from a DNA repair gene deactivation (LaCroix et al, 2014;Lenski et al, 2015); in all cases, mutation rate positively correlated with the speed of adaptation and magnitude of fitness gains.…”
Section: General Discoverymentioning
confidence: 99%
“…Adaptation to new environments requires metabolic remodeling, and HGT of metabolic genes between prokaryotes occurs at a higher rate than that of informational genes [8]; which may facilitate the recipients’ rapid adaptation [9]. Numerous metabolic pathways in eukaryotes are of bacterial origin [6], transferred from endosymbionts [10]; and many proposed HGTs between eukaryotes also involve metabolic genes [1113].…”
Section: Introductionmentioning
confidence: 99%